Lessons from the Protestant Reformation for Today’s Islamic World - Hussein Solomon; Rene de Klerk (UIN Sunan Gunung Djati Bandung, 2023)
The Muslim world is in crisis – politically, socially and economically – and Islam is in need of a reformation. Drawing on insights from the Protestant Reformation, this article argues that two of the major reasons for the success of the Protestant Reformation lay in the fact that dissident voices such as that of Martin Luther were protected and that developments like the printing press increased literacy thereby empowering ordinary people to read the Bible on their own without the Church serving as a mediator in conveying revelation to the masses. This helped to break the monopoly of the Catholic Church. At the same time, the printing press allowed the views of reformers to be disseminated to a wider audience creating widespread sympathies for the reformers given the excesses of the Church. Whilst the Muslim world shares many objective realities of the period leading to Europe’s Reformation, the reality is that reformers are provided with little protection from Muslim political elites and widespread illiteracy prevents reformist ideas from gaining traction to a wider audience.